RANCANGAN SISTEM PEMBAYARAN IURAN BULANAN SANTRI PONDOK PESANTREN DARUSSALAM MENGGUNAKAN METODE WATERFALL - Ikwan Sukirman; Juhaendi; khantaqwa Amri; Thoyyibah Tanjung (CV. Multi Kreasi Media, 2022)
Darussalam Islamic Boarding School in order to participate in spreading Islamic proselytizing in Indonesia as a traditional education, so far The Darussalam Islamic Boarding School has tried to maintain the learning of classical Islamic sciences inherited by salaf scholars. This effort to preserve traditions and modernize is a manifestation of the principle of al muhafadhah'ala al-qadim al-shalih wal akhdhu bi jadid alashlah (maintaining a good classical scientific tradition and adopting better modern science). In Pondok Pesantren we get information related to the system that will be designed to help process student / student administration data, student / student administration payment data so that it can be done more easily and more practically both offline and online. The method used in the development of this software uses a waterfall application system for monthly contribution payments at The Darussalam Islamic Boarding School, namely the creation of an Entity Relationship Diagram (ERD) and database specifications. Research conducted by Moch. Mastur Baihaqi (2011) entitled